Gastroprotection as an example: Antiadhesion against Helicobacter pylori, anti-inflammatory and antioxidant activities of aqueous extracts from the aerial parts of Lippia integrifolia Hieron - Marcial, Guillermo Emilio (2014)
ETHNOPHARMACOLOGICAL RELEVANCE: The aerial parts of Lippia integrifolia (Gris.) Hieronymus (Verbenaceae), known as incayuyo, are used by the peasant population of Argentina for treatment of diseases related to a gastrointestinal system, mainly for inflammation of the stomach and have also been included into the Argentina Food Code. This study aimed to investigate the phytochemical profile of hydrophilic extracts from the herbal material by LC-MS and to evaluate potential pharmacological mechanisms rationalizing the traditional use of incayuyo aqueous extracts potential anti-inflammatory treatment of gastrointestinal disorders. MATERIALS AND METHODS: Phytochemical profiling: LC-MS of an aqueous decoction. Antiadhesive effects against Helicobacter pylori: in vitro FACS assay using FITC-labeled bacteria and AGS human stomach cells. Influence of extracts on stomach cells and RAW 264.7 macrophages: MTT viability assay and BrdU proliferation ELISA. Influence of extracts on IL-6 and IL-8 secretion from stomach cells was quantitated by ELISA after infection of the cells with Helicobacter pylori. Influence of test extracts on macrophages: phagocytosis of FITC-labeled Zymosan particles and NO production. Antioxidative capacity: DPPH assay and O2-induced caroten oxidation. RESULTS: LC-MS profiling indicated the presence of compounds 1-20 with flavonoid hexosides, phenylethanoides (acteoside, isoacteoside) and sesquiterpenes [(epi)lippidulcine, peroxylippidulcine] in the decoction extract and subfraction PhF. The extract exhibits strong in vitro antioxidative capacity and inhibited adhesion of Helicobacter pylori to stomach cells up to 40%, while an EtOH-soluble fraction showed inhibition rates of up to 60%. Decoction increased the cellular viability of AGS cells significantly at >10 μg/mL, while proliferation rate was not influenced. Helicobacter pylori induced IL-8 secretion was significantly reduced by coincubation of AGS cells with the extracts. Aqueous extracts stimulated phagocytosis rate of macrophages and inhibited the LPS-induced NO-secretion. CONCLUSIONS: The traditional use of aqueous extracts from Lippia integrifolia for gastric inflammation seems to be rationalized: besides anti-inflammatory effects on stomach cells antiadhesive properties of the extracts against the main bacterial inductor of gastritis Helicobacter pylori were identified. Additional effects for stimulation of innate immunity and potential radical scavenging effects may additionally contribute to the activity of the extracts.